480. Outbreak of COVID-19 Among School Auction Attendees: Was it a "Silent Auction" or "Silent Transmission"?. (31st December 2020) - Rankin, Danielle A; Howard, Leigh; Fernandez, Kailee N; Talj, Rana; Haddadin, Zaid; Spieker, Andrew J; Halasa, Natasha B
Abstract: Background: One day after the pandemic was announced, Tennessee declared a state of emergency on March 12, 2020 with implementation of a stay-at-home order on March 23, 2020. Data regarding the routes and patterns of community transmission of SARS-CoV-2 are limited. We initiated an investigation after clusters of confirmed COVID-19 cases attended a large social gathering. Methods: We were notified of clinical providers who attended a "Silent School Auction" on March 7, 2020, of which several confirmed-cases were identified as targeted participants. To derive a standardized REDCap web-survey, we conducted a hypothesis-generating interview with three confirmed attendees to collect event details. Once finalized, enrollment included collecting sociodemographic, epidemiologic, and clinical data. Attendees were classified as: 1) confirmed if they had a positive SARS-CoV-2 test; 2) suspected if they developed symptoms 21-days before or after the auction; and 3) asymptomatic if no symptoms were noted. Results: From March 20-June 16, 100/166 (60%) of attendees were enrolled, with a median age of 41 years, 54% female, and 99% white. Of those, 34 and 32 were confirmed- and suspect-cases, respectively. Table 1 compares sociodemographic behaviors of all attendees, with the majority of confirmed-cases eating late in the evening. From March 6 to March 8, 58 participants reported attending other social events, of which three (i.e., church service, women's retreat, and a birthday party) were common among 43 attendees and five individuals reported onset of mild respiratory symptoms prior to the event (Figure 1) . Confirmed-cases were more likely to report having shortness of breath, chest tightness, loss of taste, loss of smell, and fever compared to suspect-cases (Figure 2) and no one required hospitalization. Dining tables from the school auction depicted a clustering of cases occurring at each table, with some individuals visiting more than one table during the event (Figure 3) . Conclusion: We identified several COVID-19 cases from a single event that occurred prior to social mitigation strategies. Our investigation highlights the importance of staying home when sick and the significance of social distancing to halt transmission of COVID-19. Disclosures: Danielle A. Rankin, MPH, CIC, Sanofi Pasteur (Grant/Research Support, Research Grant or Support) Zaid Haddadin, MD, CDC (Grant/Research Support, Research Grant or Support)Quidel Corporation (Grant/Research Support, Research Grant or Support)sanofi pasteur (Grant/Research Support, Research Grant or Support) Natasha B. Halasa, MD, MPH, Genentech (Other Financial or Material Support, I receive an honorarium for lectures - it's a education grant, supported by genetech)Karius (Consultant)Moderna (Consultant)Quidel (Grant/Research Support, Research Grant or Support)Sanofi (Grant/Research Support, Research Grant or Support)